NATIONALISM, NATION AWARENESS AND PAST IMAGINATION (A REFLECTIONS OF 65 YEAR HISTORY OF INDEPENDENT INDONESIA) - Abdulah, Anzar (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2011)
Allegations are often made ahead of the Proclamation of Independence of Indonesia, among others, is increasingly fading spirit of nationalism among the younger generation. Allegations are not necessarily true, but it has created a stigma in society. It needs to be clarified by outlining the background of the birth of nationalism and nationalism contextualization in conjunction with modern Indonesian society today. Nationalism is a long process of the dialectic between space, time and social groups, as well as the political process. Although there are its relation with the